Configuration Synthesis for Fully Restrained 7-Cable-Driven Manipulators - Xiaoqiang Tang; Lewei Tang; Jinsong Wang; Dengfeng Sun (International Journal of Advanced Robotic Systems, 2012)
Cable distribution plays a vital role in Cable Driven Parallel Manipulators (CDPMs) regarding tension and workspace quality, especially in fully restrained CDPMs. This paper focuses on three typical configurations of fully restrained CDPMs with 7 cables in order to introduce an approach for configuration synthesis. Firstly, the kinematic models of three types of CDPMs with 7 cables are set up. Then, in order to evaluate workspace quality, two new indices are proposed by using tensions along each cable, which are the All Cable Tension Distribution Index (ACTDI) and Global Tension Distribution Index (GTDI). Next, the three types of CDPMs with 7 cables are analysed with the two indices. At the end, according to different performance requirements, the configurations of cable distribution are discussed and selected.